Controversial Monuments and Memorials: A Guide for Community Leaders - Allison, David B. (Rowman & Littlefield Publishers, 2023)
The impetus for the first edition was violent actions---the white supremacist rally in Charlottesville, Virginia in 2017, which was touched off by discussions about removing a statue to Robert E. Lee, and resulted in the death of Heather Heyer. Since the publication of the first edition, both history and democracy are being threatened in ways that we were only seeing small glimpses of in 2018. Today, attempts to elevate new or more complex history has been met with vilification. States across the country have passed legislation to ban critical race theory from being taught in public schools and are seeking ways to limit what teachers are allowed to teach about slavery and race in the United States. These threats are unlikely to abate. As such, our responsibility as historians, community leaders, museum professionals, and citizens is to redouble our efforts to share human stories in relatable ways and to exercise our rights and wield our power whenever and however we can. The revised edition tackles the great issues of our time against the backdrop of monument culture and historical truth.